EFEKTIVITAS MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION (TAI) PADA MATERI KELARUTAN DAN HASIL KALI KELARUTAN TERHADAP AKTIVITAS DAN HASIL BELAJAR SISWA KELAS XI MIPA SMA NEGERI 7 PONTIANAK - Neni Meilani; Dini Hadiarti; Raudhatul Fadhilah (Universitas Muhammadiyah Pontianak, 2017)
ABSTRACTOne of the ways to increase the students activities and achievement in learning is to apply student’s oriented learning design. Therefore, this research used cooperative learning type TAI as well as evaluated its influence towards the student’s activities and achievement in learning. This research used Nonequivalent Control group design. The data was collected by using purposive sampling where XI MIPA 1 took as an experimental class and XI MIPA 3 as a controlling class. The data collected trough the use of measurement and observation techniques and the tools to collected the data was the essay and observation sheets. Based on analysis of the data which used non parametric U- Mann Whitney test showed that there was the difference on students activities and achievement in learning. The used of TAI in learning was affective to increased students activities which was 27,34% considered as moderate and the students achievement was 30,78% which was considered as high.Keywords: learning activities, learning achievement, and TAI learning model